Sistem Administrator Debt Recording Berbasis Website pada Toko Serunai Sekayu - Syahril, Muhammad; Ramdhani, M.Ficky (Jurnal Ilmu Siber dan Teknologi Digital, 2024)
Purpose: This article aims to develop and implement an administrator system for website-based debt recording that can be used by Toko Serunai Sekayu. Method: The system development method is carried out using a web-based software development approach. Development stages include requirements analysis, system design, implementation, and testing. Results: The result of this research is the successful implementation of a website-based debt recording administrator system for the Serunai Sekayu Shop. This system allows users to record customer debts efficiently and manage this data well. Limitations: The limitation of this system is its dependence on a stable internet connection for optimal access and use of the system. In addition, there may be challenges in integrating with the store's existing systems. Contribution: The main contribution of this article is the development of a specific and applicable system for debt management at Serunai Sekayu stores. This system provides a practical solution for these stores in managing and monitoring customer debt effectively through an easy-to-access web platform.